Mesoscale Plasma Convection Perturbations in the High‐Latitude Ionosphere. Issue 9 (6th September 2018) - Chen, Yun‐Ju; Heelis, Roderick A.
Abstract: An investigation of flow perturbations with spatial scale sizes between 100 and 500 km in the high‐latitude ionosphere is presented. These localized flow perturbations are deviations from the large‐scale background convection, expected to give us new insights into the magnetosphere‐ionosphere coupling process. Ion drift measurements from the Defense Meteorological Satellite Program F17 are utilized to identify these mesoscale flow perturbations. Our intent is to discover the properties of these perturbations in terms of perturbation flow speeds, location, scale size, and occurrence frequency as well as their dependence on the interplanetary magnetic field (IMF) and underlying large‐scale convection pattern. Observation suggests that flow perturbation locations strongly depend on the IMF orientation as does the occurrence frequency of the flow perturbations. For southward IMF, more flow perturbations occur in regions of sunward background flow than in regions of antisunward background flow. For flow perturbations with speeds over 300 m/s, an asymmetry in the preferred direction and scale size is seen for those embedded in sunward and antisunward background flows. Significantly less asymmetry is present for flow perturbations with speeds between 100 and 300 m/s. The flow perturbations exceeding 300 m/s are most likely closed locally with lower magnitude return flows or with adjacent flows across the convection reversal boundary and representing additional sources of frictional heating and momentum transfer to the thermosphere. The perturbation flow speed is almost independent of the scale size and underlying convection speed, but the largest speeds are preferentially seen at scale sizes between 200 and 300 km. Key Points: Flow perturbation location and occurrence frequency are dependent on the IMF B z and B y More flow perturbations occur in regions of sunward background flow than in regions of antisunward background flow for southward IMF Asymmetry in the preferred direction and scale size of flow perturbations is seen in regions of sunward and antisunward background flow